Scar sarcoidosis following rituximab therapy. Issue 6 (3rd July 2020) - Vesely, Nicole C.; Thomas, Renee M.; Rudnick, Eric; Longo, Maria Isabel
Abstract: Drug‐induced sarcoidosis has been rarely described but it constitutes a potential side effect of immunomodulatory medications. We report a case of rituximab‐induced scar sarcoidosis and review similar published cases. Although there is evidence of B‐cell dysregulation in the pathogenesis of sarcoidosis, the use of rituximab for this disease needs to be carefully evaluated based on reports of worsening and de novo development of sarcoidosis after rituximab therapy.